A REVIEW OF ENHANCE CODE QUALITY AND DEVELOPMENT EFFICIENCY BY BIG DATA INFRASTRUCTURE - Chavan, Aarati; Jaleel, Uruj; Auti, Nisha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly evolving landscape of software development, the need for high code quality and efficient development processes is paramount. The integration of Big Data infrastructure into software development workflows has emerged as a powerful approach to enhancing both code quality and development efficiency. This review explores how Big Data technologies can be leveraged to analyze vast amounts of code, identify patterns, predict potential bugs, and optimize development practices. This review underscores the transformative potential of Big Data in revolutionizing software development. The use of recommendation systems while developing software increasing in order to speed up the process of software development by software developers. Accurate recommendations leads to successful, faster, efficient development, but inaccurate recommendations can lead to inappropriate, missed deadline software development.